Score test for association between recurrent events and a terminal event. (17th February 2016) - Balan, Theodor‐Adrian; Boonk, Stephanie E.; Vermeer, Maarten H.; Putter, Hein
Abstract : The statistical analysis of recurrent events relies on the assumption of independent censoring. When random effects are used, this means, in addition, that the censoring cannot depend on the random effect. Whenever the recurrent event process is terminated by death, this assumption might not be satisfied. Because joint models arising from such situations are more difficult to fit and interpret, clinicians rarely check whether joint modeling is preferred. In this paper, we propose and compare simple, yet efficient methods for testing whether the terminal event and the recurrent events are associated or not. The performance of the proposed methods is evaluated in a simulation study, and the sensitivity to misspecification of the model is assessed. Finally, the methods are illustrated on a data set comprising repeated observations of skin tumors on T‐cell lymphoma patients. Copyright © 2016 John Wiley & Sons, Ltd.